Bajonesse Fisher’s Behaviour in Utilizing Sustainable the Mangrove Forest in Bungku Selatan, Morowali District - Siti Aisa Lamane; Anna Fatchiya; Arif Satria (Jurnal Penyuluhan, 2020)
This study aim to analyse (1) the behaviour of Bajonesse Fisher’s in making use of mangrove forest and (2) factors that influence the Bajonesse Fisher’s in utilizing the mangrove forest. This research used survey with individual analysis and conducted in Bungku Selatan District. The number of sample is 89 Bajonesse Fisher’s. The data is analysed by using descriptive statistic and correlational. The result of the study indicated that the behaviour of Bajonesse Fisher’s in utilizing of mangrove forest can be categorized fairly good as they put the sustainability aspect as priority as has been thought by their forefather for generations. Internal characteristics included ages and family size, contributed positive significantly correlated with to their behaviours of knowledge, attitudes, and actions. Socio-cultural environment included figures of adoption of costumary norms gived positive impact to their behaviour. Ecological condition of mangrove forest is moderate.